ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT PLN (PERSERO) - Jelita, Dinda; Nusantoro, Jawoto; Retnaning Rahayu, Sri (Universitas Muhammadiyah Metro, 2025)
This final project discusses the financial performance of PT PLN (Persero). This study aims to determine the financial performance of PT PLN (Persero) for the 2019-2023 period. This type of research is descriptive qualitative. The data collection technique used in this study is documentation. The data obtained by the author were analyzed using financial ratio analysis techniques so that conclusions can be drawn to answer the problems of this study. The results of this study indicate that the liquidity ratio using the Cash Ratio and Current Ratio from 2019 to 2023 can be said to be the financial condition of PT PLN (Persero) in a bad or illiquid condition, meaning that the company cannot meet its obligations to pay its short-term debts. The profitability ratio using ROA and ROE from 2019 to 2023 tends to increase but is still below the standard of good ROA and ROE values. Thus, the company's financial performance is inefficient, meaning that the company is not effective in using total assets and capital (equity) to obtain optimal profit. Solvency Ratio using DAR and DER from 2019 to 2023 can be said that financial performance is in a fairly good condition because it is still below the standard of good DAR and DER values. This shows that the smaller the percentage produced, the healthier the finances of a company.